Comparison of Performance of Magneto Hydrodynamics Generator in Presence of Hall Effect - Khatibzadeh, Ahmadali; Alizadeh Pahlavani, Mohammad reza (International Journal of Engineering and Technology, 2012)
Studying of high-temperature plasmas exposed to strong electromagnetic ?eld is Magneto Hydrodynamics. Also, it is used to obtain an electrical power. This paper proposes a simple model of MHD generator. Moreover, efficiency of different configuration of this generator is obtained by this model. Also, this paper compares different configurations of Faraday generator with the Hall generator based on their isotropic efficiency. Moreover, this model considers the effect of Hall Effect (Ion slip) on the efficiency. This analysis proof that Hall Effect decrease the efficiency in Faraday generator but increase the efficiency in the Hall generator.